Design and characterization of polycaprolactone-gelatin-graphene oxide scaffolds for drug influence on glioblastoma cells - ATASOY, BESTE MELEK; YILMAZ, BETÜL; OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN; ÜNAL YILDIRIM, SEMRA (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Three-dimensional (3D) scaffolds that mimic in vivo tumor microenvironments can be used to study tumor response to anticancer treatments, since most preclinical combination treatment strategy for anti-glioma were evaluated with traditional 2D cell culture. In this research, the nanofiber scaffolds of polycaprolactone (PCL) containing gelatin (Gel) nano/microparticles coated with different concentrations of graphene oxide (GO) and were successfully produced by combining electrospinning and electrospraying techniques. Scanning electron microscope (SEM), Fourier-transform infrared (FT-IR) spectroscopy and mechanical testing were used to characterize the structure and properties of the composites. The results show that gelatin and graphene particles can be well dispersed in the polycaprolactone nanofiber matrix by using the combination technique of electrospinning and electrospraying. The presence of 1 wt% graphene oxide increased mechanical strength of PCL/Gel scaffold and was found to be well consistent with the drug treatments (temozolomide and bortezomib) and radiotherapy by not showing additional toxicity.
Keywords: Nanocomposite; Electrospinning; Electrospraying; Graphene oxide, glioblastoma cells; 3-DIMENSIONAL SCAFFOLDS; ELECTROSPUN NANOFIBERS; FABRICATION; CHITOSAN; BORTEZOMIB; MIGRATION